prev ( testsuite > TortureTests > Complexity > complex2  ) next

Alternatives: (mml file)  (full) (simple) (plain) (form) (slideshow)
File:TortureTests/Complexity/complex2
CVS-ID:
Author:Design Science, Inc. (D. Doyle, E. Cannon, E. Tabacman, R.Miner)
Description:short complexity test

Sample Rendering:

$\begin{array}{cc}\text{Quadratic Equation}& x=\frac{-b±\sqrt{{b}_{}^{2}-4ac}}{2a}\\ \text{DisplayQuadratic Equation}& x=\frac{-b±\sqrt{{b}_{}^{2}-4ac}}{2a}\\ \text{Rational Function}& f\left(x\right)=\frac{1-{x}_{}^{2}}{1-{x}_{}^{3}}\\ \text{Rational Function}& f\left(x\right)=\frac{\left(1-{x}_{}^{2}\right){x}_{}^{3}}{1-{x}_{}^{3}}\\ \text{Rational Function}& f\left(x\right)=\frac{\left(1-{x}_{}^{2}\right)\left({x}_{}^{3}-5x\right)}{1-{x}_{}^{3}}\\ \text{Parametrize Rational Function}& f\left(x\right)=\frac{\left({a}_{i}^{}-{x}_{}^{2}{\right)}_{}^{5}}{1-{x}_{}^{3}}\\ \text{Stacked exponents}& g\left(z\right)={e}_{}^{-{x}_{}^{2}}\\ \text{Stacked exponents}& g\left(z\right)={e}_{}^{-\left(z-a{\right)}_{}^{2}}\\ \text{Stacked exponents}& g\left(z\right)={e}_{}^{-\sum _{i=0}^{\infty }{z}_{i}^{2}}\\ \text{Stacked exponents}& g\left(y\right)={e}_{}^{-\sum _{i=0}^{\infty }{y}_{i}^{2}}\\ \text{Stacked exponents}& g\left(z\right)={e}_{}^{-\sum _{i=0}^{\infty }{z}_{}^{\frac{2}{a-i}}}\\ \text{Cross Product}& \frac{{x}_{1}^{}-{x}_{2}^{}}{{x}_{3}^{}-{x}_{4}^{}}\frac{{x}_{1}^{}-{x}_{4}^{}}{{x}_{2}^{}-{x}_{3}^{}}\\ \text{Cross Product}& \left(\frac{{x}_{1}^{}-{x}_{2}^{}}{{x}_{3}^{}-{x}_{4}^{}}\right)\left(\frac{{x}_{1}^{}-{x}_{4}^{}}{{x}_{2}^{}-{x}_{3}^{}}\right)\\ \text{Cross Product}& \left(\frac{{x}_{1}^{}-{x}_{2}^{}}{{x}_{3}^{}-{x}_{4}^{}}\right)\left(\frac{{x}_{1}^{}-{x}_{4}^{}}{{x}_{2}^{}-{x}_{3}^{}}\right)\\ \text{Cross Product}& \frac{\left({x}_{1}^{}-{x}_{2}^{}\right)\left({x}_{3}^{}-{x}_{4}^{}\right)}{\left({x}_{1}^{}-{x}_{4}^{}\right)\left({x}_{2}^{}-{x}_{3}^{}\right)}\end{array}$

Source Code:

```<math xmlns="http://www.w3.org/1998/Math/MathML">
<mtable>
<mtr>
<mtd>
</mtd>
<mtd>
<mrow>
<mi>x</mi>
<mo>=</mo>
<mfrac>
<mrow>
<mo>-</mo>
<mi>b</mi>
<mo>&#x00B1;</mo>
<msqrt>
<mrow>
<msubsup>
<mi>b</mi>
<mrow/>
<mn>2</mn>
</msubsup>
<mo>-</mo>
<mn>4</mn>
<mi>a</mi>
<mi>c</mi>
</mrow>
</msqrt>
</mrow>
<mrow>
<mn>2</mn>
<mi>a</mi>
</mrow>
</mfrac>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
</mtd>
<mtd>
<mstyle displaystyle="true">
<mi>x</mi>
<mo>=</mo>
<mfrac>
<mrow>
<mo>-</mo>
<mi>b</mi>
<mo>&#x00B1;</mo>
<msqrt>
<mrow>
<msubsup>
<mi>b</mi>
<mrow/>
<mn>2</mn>
</msubsup>
<mo>-</mo>
<mn>4</mn>
<mi>a</mi>
<mi>c</mi>
</mrow>
</msqrt>
</mrow>
<mrow>
<mn>2</mn>
<mi>a</mi>
</mrow>
</mfrac>
</mstyle>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Rational Function</mtext>
</mtd>
<mtd>
<mrow>
<mi>f</mi>
<mo stretchy="false">(</mo>
<mi>x</mi>
<mo stretchy="false">)</mo>
<mo>=</mo>
<mfrac>
<mrow>
<mn>1</mn>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>2</mn>
</msubsup>
</mrow>
<mrow>
<mn>1</mn>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>3</mn>
</msubsup>
</mrow>
</mfrac>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Rational Function</mtext>
</mtd>
<mtd>
<mrow>
<mi>f</mi>
<mo stretchy="false">(</mo>
<mi>x</mi>
<mo stretchy="false">)</mo>
<mo>=</mo>
<mfrac>
<mrow>
<mo stretchy="false">(</mo>
<mn>1</mn>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>2</mn>
</msubsup>
<mo stretchy="false">)</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>3</mn>
</msubsup>
</mrow>
<mrow>
<mn>1</mn>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>3</mn>
</msubsup>
</mrow>
</mfrac>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Rational Function</mtext>
</mtd>
<mtd>
<mrow>
<mi>f</mi>
<mo stretchy="false">(</mo>
<mi>x</mi>
<mo stretchy="false">)</mo>
<mo>=</mo>
<mfrac>
<mrow>
<mo stretchy="false">(</mo>
<mn>1</mn>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>2</mn>
</msubsup>
<mo stretchy="false">)</mo>
<mo stretchy="false">(</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>3</mn>
</msubsup>
<mo>-</mo>
<mn>5</mn>
<mi>x</mi>
<mo stretchy="false">)</mo>
</mrow>
<mrow>
<mn>1</mn>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>3</mn>
</msubsup>
</mrow>
</mfrac>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Parametrize Rational Function
</mtext>
</mtd>
<mtd>
<mrow>
<mi>f</mi>
<mo stretchy="false">(</mo>
<mi>x</mi>
<mo stretchy="false">)</mo>
<mo>=</mo>
<mfrac>
<mrow>
<mo stretchy="false">(</mo>
<msubsup>
<mi>a</mi>
<mi>i</mi>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>2</mn>
</msubsup>
<msubsup>
<mo stretchy="false">)</mo>
<mrow/>
<mn>5</mn>
</msubsup>
</mrow>
<mrow>
<mn>1</mn>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>3</mn>
</msubsup>
</mrow>
</mfrac>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Stacked exponents</mtext>
</mtd>
<mtd>
<mrow>
<mi>g</mi>
<mo stretchy="false">(</mo>
<mi>z</mi>
<mo stretchy="false">)</mo>
<mo>=</mo>
<msubsup>
<mi>e</mi>
<mrow/>
<mrow>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mrow/>
<mn>2</mn>
</msubsup>
</mrow>
</msubsup>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Stacked exponents</mtext>
</mtd>
<mtd>
<mrow>
<mi>g</mi>
<mo stretchy="false">(</mo>
<mi>z</mi>
<mo stretchy="false">)</mo>
<mo>=</mo>
<msubsup>
<mi>e</mi>
<mrow/>
<mrow>
<mo>-</mo>
<mo stretchy="false">(</mo>
<mi>z</mi>
<mo>-</mo>
<mi>a</mi>
<msubsup>
<mo stretchy="false">)</mo>
<mrow/>
<mn>2</mn>
</msubsup>
</mrow>
</msubsup>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Stacked exponents</mtext>
</mtd>
<mtd>
<mrow>
<mi>g</mi>
<mo stretchy="false">(</mo>
<mi>z</mi>
<mo stretchy="false">)</mo>
<mo>=</mo>
<msubsup>
<mi>e</mi>
<mrow/>
<mrow>
<mo>-</mo>
<munderover>
<mo>&#x2211;</mo>
<mrow>
<mi>i</mi>
<mo>=</mo>
<mn>0</mn>
</mrow>
<mi>&#x221E;</mi>
</munderover>
<msubsup>
<mi>z</mi>
<mi>i</mi>
<mn>2</mn>
</msubsup>
</mrow>
</msubsup>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Stacked exponents</mtext>
</mtd>
<mtd>
<mrow>
<mi>g</mi>
<mo stretchy="false">(</mo>
<mi>y</mi>
<mo stretchy="false">)</mo>
<mo>=</mo>
<msubsup>
<mi>e</mi>
<mrow/>
<mrow>
<mo>-</mo>
<munderover>
<mo>&#x2211;</mo>
<mrow>
<mi>i</mi>
<mo>=</mo>
<mn>0</mn>
</mrow>
<mi>&#x221E;</mi>
</munderover>
<msubsup>
<mi>y</mi>
<mi>i</mi>
<mn>2</mn>
</msubsup>
</mrow>
</msubsup>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Stacked exponents</mtext>
</mtd>
<mtd>
<mrow>
<mi>g</mi>
<mo stretchy="false">(</mo>
<mi>z</mi>
<mo stretchy="false">)</mo>
<mo>=</mo>
<msubsup>
<mi>e</mi>
<mrow/>
<mrow>
<mo>-</mo>
<munderover>
<mo>&#x2211;</mo>
<mrow>
<mi>i</mi>
<mo>=</mo>
<mn>0</mn>
</mrow>
<mi>&#x221E;</mi>
</munderover>
<msubsup>
<mi>z</mi>
<mrow/>
<mfrac>
<mn>2</mn>
<mrow>
<mi>a</mi>
<mo>-</mo>
<mi>i</mi>
</mrow>
</mfrac>
</msubsup>
</mrow>
</msubsup>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Cross Product</mtext>
</mtd>
<mtd>
<mrow>
<mfrac>
<mrow>
<msubsup>
<mi>x</mi>
<mn>1</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>2</mn>
<mrow/>
</msubsup>
</mrow>
<mrow>
<msubsup>
<mi>x</mi>
<mn>3</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>4</mn>
<mrow/>
</msubsup>
</mrow>
</mfrac>
<mfrac>
<mrow>
<msubsup>
<mi>x</mi>
<mn>1</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>4</mn>
<mrow/>
</msubsup>
</mrow>
<mrow>
<msubsup>
<mi>x</mi>
<mn>2</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>3</mn>
<mrow/>
</msubsup>
</mrow>
</mfrac>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Cross Product</mtext>
</mtd>
<mtd>
<mrow>
<mo stretchy="false">(</mo>
<mfrac>
<mrow>
<msubsup>
<mi>x</mi>
<mn>1</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>2</mn>
<mrow/>
</msubsup>
</mrow>
<mrow>
<msubsup>
<mi>x</mi>
<mn>3</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>4</mn>
<mrow/>
</msubsup>
</mrow>
</mfrac>
<mo stretchy="false">)</mo>
<mo stretchy="false">(</mo>
<mfrac>
<mrow>
<msubsup>
<mi>x</mi>
<mn>1</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>4</mn>
<mrow/>
</msubsup>
</mrow>
<mrow>
<msubsup>
<mi>x</mi>
<mn>2</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>3</mn>
<mrow/>
</msubsup>
</mrow>
</mfrac>
<mo stretchy="false">)</mo>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Cross Product</mtext>
</mtd>
<mtd>
<mrow>
<mo>(</mo>
<mfrac>
<mrow>
<msubsup>
<mi>x</mi>
<mn>1</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>2</mn>
<mrow/>
</msubsup>
</mrow>
<mrow>
<msubsup>
<mi>x</mi>
<mn>3</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>4</mn>
<mrow/>
</msubsup>
</mrow>
</mfrac>
<mo>)</mo>
<mo>(</mo>
<mfrac>
<mrow>
<msubsup>
<mi>x</mi>
<mn>1</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>4</mn>
<mrow/>
</msubsup>
</mrow>
<mrow>
<msubsup>
<mi>x</mi>
<mn>2</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>3</mn>
<mrow/>
</msubsup>
</mrow>
</mfrac>
<mo>)</mo>
</mrow>
</mtd>
</mtr>
<mtr>
<mtd>
<mtext>Cross Product</mtext>
</mtd>
<mtd>
<mfrac>
<mrow>
<mo stretchy="false">(</mo>
<msubsup>
<mi>x</mi>
<mn>1</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>2</mn>
<mrow/>
</msubsup>
<mo stretchy="false">)</mo>
<mo stretchy="false">(</mo>
<msubsup>
<mi>x</mi>
<mn>3</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>4</mn>
<mrow/>
</msubsup>
<mo stretchy="false">)</mo>
</mrow>
<mrow>
<mo stretchy="false">(</mo>
<msubsup>
<mi>x</mi>
<mn>1</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>4</mn>
<mrow/>
</msubsup>
<mo stretchy="false">)</mo>
<mo stretchy="false">(</mo>
<msubsup>
<mi>x</mi>
<mn>2</mn>
<mrow/>
</msubsup>
<mo>-</mo>
<msubsup>
<mi>x</mi>
<mn>3</mn>
<mrow/>
</msubsup>
<mo stretchy="false">)</mo>
</mrow>
</mfrac>
</mtd>
</mtr>
</mtable>
[/itex]```